Human adipose-derived mesenchymal stem cells for osteoarthritis: a pilot study with long-term follow-up and repeated injections. (8th February 2018) - Song, Yang; Du, Hui; Dai, Chengxiang; Zhang, Li; Li, Suke; Hunter, David J; Lu, Liangjing; Bao, Chunde
Aim: This study aimed to evaluate the safety and therapeutic potential of autologous human adipose-derived mesenchymal stem cells (haMSCs) in patients with osteoarthritis.Materials & methods: Safety and efficacy of haMSCs were preclinically assessed in vitro and in BALB/c-nu nude mice. 18 patients were enrolled and divided into three dose groups: the low-dose, mid-dose and high-dose group (1 × 10 7, 2 × 10 7 and 5 × 10 7 cells, respectively), provided three injections and followed up for 96 weeks.Results & Conclusion: The preclinical study established the safety and efficacy of haMSCs. Intra-articular injections of haMSCs were safe and improved pain, function and cartilage volume of the knee joint, rendering them a promising novel treatment for knee osteoarthritis. The dosage of 5 × 10 7 haMSCs exhibited the highest improvement (ClinicalTrials.gov Identifier: NCT01809769).